Melatonin and Alzheimer's Disease - Abdullayeva N.N; Kasimov A.A.; Eshpo’latov Sh. S.; Norbekov B. Sh. (Scholars Digest Publishing, 2023)
Alzheimer's disease (AD) is the most common cause of severe cognitive impairment in old age among organic brain lesions. Given the progressive aging of the population in industrialized countries and the increasing number of people suffering from AD, the problem of its pathogenesis and treatment becomes not only of medical, but also of social importance.
Keywords: Alzheimer's disease, epiphysis, melatonin.